Biomarkers, diagnostics and precision medicine in the drug industry : critical challenges, limitations and roadmaps for the best practices - Halim, Abdel (Academic Press, 2019)
The high failure rate in the pharmaceutical industry has positioned biomarkers and personalized medicine in the frontline, as possible solutions. If executed right, biomarkers and companion diagnostics (CDx) can potentially help the drug industry enhance the probability of success, accelerate the time to market, and, more importantly, benefit patients by supporting accurate diagnosis and selection of the most effective and least toxic therapies. This book aims to examine the challenges and limitations in biomarkers and laboratory tests. It also offers advice on best practices to ensure proper application of biomarkers and bridges the gap between diagnostic business development claims and real-life deliverables. The book covers biomarkers for different purposes, provides examples from different technologies, which includes standard-of-care approved assays as well as for-investigational-use and for-research-use-only assays. It also includes new data for biomarkers in different therapeutic indications and offers case studies and practical examples. This book serves as a reference to drug developers, IVD providers, clinical labs, healthcare givers, academicians, and researchers for best practices to help increase the probability of success in drug development and improve patient management.